PENGARUH SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PT. BANGKINANG DI PEKANBARU (STUDI KASUS PADA KARYAWAN TETAP PT. BANGKINANG) - Ishak Syahropi; KasmiruDdin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of the spirit of work on the performance of employees on permanent employees at PT. Bangkinang .spirit of work as the independent variable ( x ) has been formulated that is seen on the level of absenteeism , job satisfaction , cooperation , and discipline, while the employee's performance as the dependent variable ( y ) . this research was carried out on all permanent employees at PT. Bangkinang many as 44 people .Data obtained from questionnaires and subsequently processed to then be tested using statistical analysis as a simple linear regression analysis, t test, and correlation analysis and determination using spss.The results showed that the results of hypothesis testing t greater than t table is 11.205 >1.998 .this shows that the morale effect on employee performance . the amount effect of the spirit of work on the performance of employeeson permanent employees at PT.Bangkinang is 73.8 % .Keywords: Spirit Of Work, Employee Performance